Endometriosis and the microbiome: a systematic review. (19th September 2019) - Leonardi, M; Hicks, C; El‐Assaad, F; El‐Omar, E; Condous, G
Abstract : Background: The aetiology and pathogenesis of endometriosis are still under investigation. There is evidence that there is a complex bidirectional interaction between endometriosis and the microbiome. Objective: To systematically review the available literature on the endometriosis–microbiome interaction, with the aim of guiding future inquiries in this emerging area of endometriosis research. Search strategy: MEDLINE, Embase, Scopus and Web of Science were searched through May 2019. A manual search of reference lists of relevant studies was also performed. Selection criteria: Published and unpublished literature in any language describing a comparison of the microbiome state in mammalian hosts with and without endometriosis. Data collection and analysis: Identified studies were screened and assessed independently by two authors. Data were extracted and compiled in a qualitative synthesis of the evidence. Main results: Endometriosis appears to be associated with an increased presence of Proteobacteria, Enterobacteriaceae, Streptococcus spp. and Escherichia coli across various microbiome sites. The phylum Firmicutes and the genus Gardnerella also appear to have an association; however, this remains unclear. Conclusions: The complex bidirectional relationship between the microbiome and endometriosis has begun to be characterised by the studies highlighted in this systematic review. Laboratory and clinical studies demonstrate that there are indeed differences in the microbiome composition of hosts with and without endometriosis. Tweetable abstract: Review findings show endometriosis associated with increased Proteobacteria, Enterobacteriaceae, Streptococcus and Escherichia coli across various microbiome sites. Tweetable abstract: Review findings show endometriosis associated with increased Proteobacteria, Enterobacteriaceae, Streptococcus and Escherichia coli across various microbiome sites.